THE INFLUENCE OF BUSINESS LOCATION, ADVERTISING, AND SERVICE QUALITY AGAINST PURCHASING DECISIONS - Ricky Rafii Ritonga; Cristina Reinaldo; Yosella Winaldi; Jenniffer -; Edisah Putra Nainggolan (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Analyzing and knowing how much influence business location, advertising and service quality have on purchasing decisions that occur at Maju Bersama Supermarkets is the goal of this study. Researchers used associative approach research methods and quantitative research types. Analyzing the data in this study with multiple regression analysis. Data collection techniques were applied with questionnaires, interviews and documentation studies. The research population is visitors who have shopped at the Maju Bersama Supermarket which is also used as a sample of 142 consumers. The slovin formula is used to determine the number of samples. The t(count) value of the Business Location variable is -2.516, Advertising is 1.028, and Service Quality is 4.399 and F(count) is 8.754. The research results show that the coefficient of determination is 16%. The conclusion in this study is that simultaneously and partially Business Location, Advertising and Service Quality have a significant and positive value effect on Purchasing Decisions at PT. Maju Bersama Supermarket